2018
DOI: 10.1186/s12870-018-1417-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring transcription factors reveals crucial members and regulatory networks involved in different abiotic stresses in Brassica napus L.

Abstract: BackgroundBrassica napus (B. napus) encompasses diverse transcription factors (TFs), but thorough identification and characterization of TF families, as well as their transcriptional responsiveness to multifarious stresses are still not clear.ResultsTotally 2167 TFs belonging to five families were genome-widely identified in B. napus, including 518 BnAP2/EREBPs, 252 BnbZIPs, 721 BnMYBs, 398 BnNACs and 278 BnWRKYs, which contained some novel members in comparison with existing results. Sub-genome distributions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 75 publications
1
38
0
Order By: Relevance
“…Wild relatives may provide new gene resources for improving drought tolerance of crops. RNA-seq is a useful approach for the identification of DEGs in a regulatory network at the transcriptome level, which provides insights into the molecular mechanisms in response to abiotic stresses [32]. Through the transcriptomic analysis of the maize seedling leaves under salinity, drought, heat, and cold stresses, the responses were found to be mediated by pathways involving hormone metabolism and signaling, transcription factors (TFs), very-long-chain fatty acid biosynthesis and lipid signaling [33].…”
Section: Discussionmentioning
confidence: 99%
“…Wild relatives may provide new gene resources for improving drought tolerance of crops. RNA-seq is a useful approach for the identification of DEGs in a regulatory network at the transcriptome level, which provides insights into the molecular mechanisms in response to abiotic stresses [32]. Through the transcriptomic analysis of the maize seedling leaves under salinity, drought, heat, and cold stresses, the responses were found to be mediated by pathways involving hormone metabolism and signaling, transcription factors (TFs), very-long-chain fatty acid biosynthesis and lipid signaling [33].…”
Section: Discussionmentioning
confidence: 99%
“…To adapt to adverse environmental conditions, many plants have developed different mechanisms in response to abiotic stresses. Most transcription factors (TFs) can act as regulatory proteins that play an important role in these mechanisms (Wang, Yang, et al, 2018). For example, the TIFY family is a novel plant‐specific gene family that participates in the regulation of various plant‐specific biologic processes (Sun et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We selected one of seven genes in the bHLH family (Nitab4.5_0000093g0110) for study using RNAi, finding the resultant plant showed an altered nicotine level (unpublished data), and implying an important regulatory role in nicotine biosynthesis. Other newly identified AP2/ EREBP, bHLH, WRKY, ARF, MYB, and NAC TF genes might also be involved in nicotine biosynthesis, since all of these TF families have been described as functioning in the regulation of plant secondary metabolism [45][46][47]. These are therefore good targets for further experiments.…”
Section: Differential Expressed Transcription Factors Related To Regumentioning
confidence: 99%